Modified Lich-Gregoir Ureteral Reimplantation for the Treatment of Unilateral Primary Vesicoureteral Reflux in Pediatric Patients: A Comparative Analysis with Medium-Term outcomes - Guler, Yavuz; Erbin, Akif; Ozmerdiven, Gokhun (Urology Journal, 2020)
Purpose: To present the medium-term results for the modified Lich-Gregoir (LG) reimplantation technique in the treatment of unilateral primary vesicoureteral reflux (VUR) by comparing patients under and over 12 months of age. Materials and Methods: Data for patients who underwent modified LG surgery between January 2006 and December 2018 were retrospectively reviewed from the hospital data-recording system and patients under the age of 18 years were included in the study. After exclusion criteria, 55 patients in total were included in advanced analysis. The patients were grouped as ≤12 months and >12 months. Demographic characteristics, operative, and postoperative follow-up data were comparatively analyzed. Results: The mean±SD (range) of age was 10.4 ± 2.8 (6-12) and 41.4 ± 18.5 (13-96) months in the ≤12 months and >12 months groups, respectively. Mean operation time and hospitalization time were not significant between the groups. Mean follow-up times were 39.5 ± 14.1 and 38.4 ± 13.2 months, in the ≤12 months and >12 months groups, respectively. There was no difference in terms of complications between the groups and all of the complications in both groups were in grade 1 category according to the Modified Clavien complication classification. One (6.6%) patient in the ≤12 months group and 3 (7.5%) patients in the >12 months group had late (>30 days) febrile UTI, but none of them had a recurrence of VUR. Febrile infection did not recur during the follow-up period in these patients. While recurrent VUR was not seen in any patient in the ≤12 months group (success: 100%), it was observed in 2 (5%) patients in the >12 months group (success rate: 95%) (p = 0.38). Conclusion: The open LG ureteral reimplantation technique is an effective procedure for the treatment of unilateral primary VUR in children both under 12 months and over 12 months of age with minor morbidity.